1999
DOI: 10.1046/j.1365-2036.1999.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the pharmacology of rabeprazole

Abstract: Rabeprazole sodium is a new substituted benzimidazole proton pump inhibitor with several differences compared with existing proton pump inhibitors. In vitro and animal studies have demonstrated that rabeprazole is a more potent inhibitor of H+,K(+)-ATPase and acid secretion than omeprazole, and is a more rapid inhibitor of proton pumps than omeprazole, lansoprazole, or pantoprazole. This probably reflects rabeprazole's faster activation in the parietal cell canaliculus. In human studies, once-daily doses of 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 36 publications
0
74
0
Order By: Relevance
“…[97,[101][102][103][104][105][106][107] Thus, the MIC range against H. pylori for rabeprazole is considerably lower than that previously reported for omeprazole or lansoprazole. [97,[101][102][103][104][105][106][107][108] Furthermore, in vitro, rabeprazole inhibits H. pylori motility [105,106] and urease activity. [109,110] However, but for some exceptions, rabeprazole monotherapy has not been able to eradicate H. pylori infection.…”
Section: Rabeprazolementioning
confidence: 98%
See 3 more Smart Citations
“…[97,[101][102][103][104][105][106][107] Thus, the MIC range against H. pylori for rabeprazole is considerably lower than that previously reported for omeprazole or lansoprazole. [97,[101][102][103][104][105][106][107][108] Furthermore, in vitro, rabeprazole inhibits H. pylori motility [105,106] and urease activity. [109,110] However, but for some exceptions, rabeprazole monotherapy has not been able to eradicate H. pylori infection.…”
Section: Rabeprazolementioning
confidence: 98%
“…[62,[95][96][97][98][99] However, this PPI has shown itself to have a greater anti-secretory potency and is associated with a faster onset of action than other PPIs (such as omeprazole) at equivalent doses. [62,[95][96][97][98][99] This PPI has been shown to have high anti-secretory efficacy in H. pylori-infected subjects. [100] On the other hand, a number of studies have shown that rabeprazole shows greater 88 Gisbert Fig.…”
Section: Rabeprazolementioning
confidence: 99%
See 2 more Smart Citations
“…PPIs are completely eliminated after hepatic biotransformation. Elimination is predominantly via bile [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%